Pengembangan Usaha Penangkapan Ikan Tuna di Kota Sorong Papua Barat - Sudirman Sudirman (Jurnal Airaha, 2017)
A Developing Tuna Fishing Technology in Sorong in West Papua. This study aims to analyze the feasibility and the factors of production that affect the business unit of tuna fishing with hand line, either individually or in groups with a placeholders ship and develop strategy of tuna fishing in the city of Sorong in West Papua. The study was implemented in January to June 2012 at Sorong in West Papua. The data were collected throuhgt surveys,observations,interview and questionnaires to 30 hand line fisherman in Sorong randomly, and by Followed the fishing operation in the placeholders ships. The feasibility were analyzed throught the Net Present Value (NVP),Net Benefit / Cost Ratio(Net B/C) and Internal Rate of Return (IRR), while to determine the factors that influence the production, could be analyzed by multiple linear regression analysis and stepwise analysis with Minitab 15.To determine the development strategies, analyzed by the SWOT analysis. These results indicates that tuna fishing with rod elongation either individually or in groups with placeholders ship is feasible because NVP> 0, IRR> DF and Net B/C> 1. Viewed from the income of fisherman, tuna fishing effort in the group is more profitable, because the income of individual fisherman is Rp. 24,745,252.00 / year / fisherman, while the income of fisherman with a placeholder ship is Rp. 45,524,640.00 /year /fisherman